University extension: the possibility of a liberating praxis by the ethics of care - Wahlbrinck, Iliria François; Pacheco, Luci Mary Duso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
In this study we aim to get to know if the effectiveness of the Ethics of Care in University Extension projects enables dialogue on liberating educational practices. In order to it, we use a qualitative approach and bibliographical studies in the construction and analysis of a theoretical framework that enables the understanding of care as constitutive of the human being in the university context and practice. University is the institution where the formation of leaders committed to the transformation of what does not contribute to the dignity of life occurs. In it, teaching-research-extension should be developed inseparable. Education is basic academic formation; theoretical support that bases research and extension. Research is an activity focused on problem solving; is search and inquest. Extension is an educational, cultural and scientific process; articulator between teaching and research. It is permanent bridge between the community and the University, where both learn through dialogue and exchange of knowledge. Committed to an education that forms to transform, the extension action can configure a liberating, caregiver pedagogical practice. The contemplation of the Ethics of Care in its development provides opportunities for transformation through the execution of humanizing praxis in a historical and social context where the university is inserted.